Natural “Natural Experiments” in Economics - Rosenzweig, Mark R; Wolpin, Kenneth I (Journal of Economic Literature, 2000)
The recent literature exploiting natural events as “natural experiment” instruments is reviewed to assess to what extent it has advanced empirical knowledge. A weakness of the studies that adopt this approach is that the necessary set of behavioral, market, and technological assumptions made by the authors in justifying their interpretations of the estimates is often absent. The methodology and findings from twenty studies are summarized and simple economic models are used to elucidate the implicit assumptions made by the authors and to demonstrate the sensitivity of the interpretations of the findings to the relaxation of some of these assumptions.